E-Commerce of Online Store Application at Kstore Kalbis Insitute - Purwandari, Nuraini (International Humanities and Applied Science Journal, 2019)
Kalbis Institute Cooperative is an association established at Kalbis Institute, one of the private universities in East Jakarta. One of the business activities in this Cooperative is buying and selling merchandise contained in a store called Kstore. Currently, the Kstore sales system is still conventional waiting for customers to come to the store so it is less effective because the customer must come directly to the store to find and choose the desired goods. E-commerce is a process of selling and purchasing products or services that are done electronically through a computer network or internet. E-commerce can be used in managing Kstore to improve and simplify business process activities. This study aims to build Kstore merchandise buying application online. System development method used is Web Development Life Cycle (WDLC). The results of this research is e-commerce website to facilitate customers in conducting transactions as well as promotions or product offerings, and ordering products anytime and anywhere by utilizing internet technology.